A history of political thought : from ancient Greece to early Christianity / Janet Coleman. - Coleman, Janet, 1945- (Blackwell, 2000)
In this history of European political thought, the author strikes a balance between trying to understand the philosophical cogency of ancient arguments and elucidating why the ancient Greeks and Romans thought the way they did about politics.